The Influence of Brand Love and Brand Image on Brand Loyalty and Willingness to Pay a Premium Price Among Buttonscarves Hijab Users - Putri, Andina Fitriasiska; Rahmawati, Rahmawati; Adhimursandi, Doddy (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of premium Muslim fashion trends has attracted consumers' attention to premium hijab brands, including Buttonscarves, which is known for building emotional closeness and a positive image among its users. This situation has created a need to understand the role of consumer psychological factors in determining their behavior towards premium products. In an effort to understand this phenomenon, research was conducted to determine the extent to which brand love and brand image can influence customer loyalty and their willingness to pay higher prices. The method used was a quantitative approach through a survey of 150 Buttonscarves users, which was then analyzed with SEM to see the relationship between variables simultaneously. The results of the study provide evidence that the higher the level of love and positive image towards the brand, the greater the consumer loyalty and their willingness to accept premium prices. Although loyalty does not directly encourage consumers to pay more, loyalty still acts as a mediating channel that strengthens the influence of brand love and image on premium behavior. Thus, this study emphasizes that branding strategies that foster emotional bonds and positive perceptions are crucial for premium brands like Buttonscarves to maintain their competitive edge and market value.